INHERITANCE RIGHTS PROTECTION FOR FETUS IN UTERO THROUGH TRUST-LIKE MECHANISM AS A NORMATIVE SOLUTION IN INDONESIAN - Rayi Kharisma Rajib; Chatrine Novianti Sitanggang; Veny Gambini Tampubolon (Law Research Review Quarterly, 2026)
The regulation of inheritance rights for a fetus in utero has been recognized under the Kitab Undang-Undang Hukum Perdata (KUHPerdata) through the principle of nasciturus pro iam nato habetur, which grants a conditional legal status provided the fetus is subsequently born alive. However, this recognition lacks an adequate legal mechanism to ensure the management and protection of inherited assets during the period when the legal subject is not yet capable of exercising those rights. This study employs a juridical normative method with conceptual, statutory, and comparative approaches to analyze the normative weaknesses in the existing regulation and to formulate a trust-like mechanism as an adaptive solution within the Indonesian civil law system. The analysis reveals five structural weaknesses in the current regulation: ambiguity in gestational age verification, absence of interim asset management mechanisms, inconsistency with child.